THE ROLE OF MENTOR IN MENTORING FRESH GRADUATED NURSES - cicilia nony ayuningsih bratajaya; ernawati sitompul (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2021)
The transition process of fresh graduated nurses from nursing student become nurse, it could be challenging especially in this generation which facing of technology acceleration, in the other hand as a nurse should be humanist. Someone who has good cognitive and technical skills, but without adequate mentoring, it would be difficult to endure adaptation process successfully. Therefore, a mentor would play important role to guide the novice nurses in dealing with situations in the work environment. Objective: This study aims to explore the experience of mentors in hospitals in mentoring beginner nurses. Methods: This qualitative research uses interpretive phenomenology by using Gadamer's philosophical hermeneutics as a methodology. The data collected through semi-structured interviews. The samples of this study were 8 nurses from several unit in a hospital.Results: This study resulted in three themes: mentoring process; mentor roles and functions; and challenges of a mentor. Discussion: One of challenging mentoring is short duration of mentoring due to rush hour in a ward. Unsuccsessful mentoring could contribute the difficulty of fresh graduated nurse to adapt on working life. Conclusion: Mentor commitment in mentoring fresh graduated nurse on the transition and adaptation of working should be supported by positive corporate culture and synergistically with institution policy. Keywords: Mentoring,Challenges of Mentor, Mentor Roles and Functions, Adaptation of fresh graduated nurses